Content validity of D-MESS: Articulate storyline 3-based learning media in sport massage courses - Tisna MS, Gede Doddy; Kusuma, Ketut Chandra Adinata; Muliarta, I Wayan; Darmawan, Gede Eka Budi (UIR Press, 2023)
The development of innovative learning media is one of the solutions for educators in the learning process in higher education in the current era of digital and technological disruption. Interactive learning media are relevant to be applied in hybrid or blended learning methods. The purpose of this study was to find out the results of validating D-MESS content as an interactive learning medium in sports massage courses. The data used in this study are quantitative data obtained from questionnaires filled out by learning experts, media experts, and programming experts. The data analysis technique used is quantitative descriptive, which is oriented towards the Content Validity Index (CVI) approach. The results of the validation test on D-MESS show that, from the educational aspect, a value of 0.89 is obtained, on the aspect of program display, a value of 0.91, and on the aspect of technical quality, a value of 0.83. Referring to these results, the interactive learning media for the sports massage course, which is named D-MESS, has a high level of validation, both from the educational aspect, program appearance, and technical quality. So that the relevance of all components of the three aspects, such as curriculum suitability, content of learning materials, interaction, feedback, coloring, graphics, sound, animation, display between screens, ease of use, and program security, is very good, even though there are minor revisions. Furthermore, with this very high D-MESS validation value, it is suggested for future research.